Nationwide trends and in-hospital complications of trachelectomy for surgically resectable cervical cancer in Taiwanese women: A population-based study, 1998-2013 - Jerry Cheng-Yen Lai; Hung-Hui Chen; Kuei-Hui Chu; Chia-Sui Weng; Yiing-Jenq Chou; Nicole Huang; Yu-Ju Chien; Kung-Liahng Wang (Elsevier, 2017)
Objective: To describe the nationwide trends in the utilization of trachelectomy among Taiwanese women with surgically resectable cervical cancer over the past decade, and to compare associated demographic characteristics, in-hospital complications and related outcomes using a population-based dataset from 1998 to 2013. Materials and methods: We conducted a population-based, cohort study using inpatient admission claims data of Taiwan's National Health Insurance program. Women who underwent trachelectomy for cervical cancers were compared by age at surgery (younger than 40 years, 40-59 years, and 60 years or older). Results: Our study cohort consisted of 156 women. The overall utilization increased considerably during the study period, particularly in younger women aged 30-39 years. Compared with older women who had trachelectomy, women younger than 40 years were diagnosed more frequently in the later years of study (2007-2013, 69.9% vs 37.3%), were treated more frequently at medical centers (89.0% vs 60.2%) by physicians aged 55 years or older (50.7% vs 22.9%) with high case volume (50.7% vs 26.5%), were less likely to undergo concomitant surgeries for bilateral oophorectomy (1.4% vs 21.7%) and lysis of peritoneal adhesion (2.7% vs 24.1%), and were more likely to undergo lymph node excision (74.0% vs 47.0%) (P < 0.05 for all). During a median of follow-up of 5.4 (2.4-9.5) years, 5.1% received future hysterectomy after trachelectomy (n = 8) with a median time-to-future hysterectomy of 0.6 (0.2-5.0) years. The estimated risks of disease recurrence for cervical cancer and readmission within 30-days (n = 35) were 3.8% and 22.4%, respectively. Women's age at trachelectomy had no apparent association with the length of hospital stay (P = 0.11), in-hospital mortality, readmission within 30-days (P = 0.33), future hysterectomy (P = 0.14), and in-hospital complications (P = 0.47). Conclusion: Substantial increase in the trend of delayed childbearing may have influenced the decision-making of Taiwanese women with cervical cancer in favor of trachelectomy over hysterectomy over the past 16-years from 1998 to 2013. When considering the uterine preservation for future fertility, women should be counseled about the risk of disease recurrence for cervical cancer before making surgical decision for trachelectomy over hysterectomy.